Whole genome sequencing, variant analysis, phylogenetics, and deep sequencing of Zika virus strains - Susmita Shrivastava (Nature Portfolio, 2018)
Abstract The recent emergence of Zika virus (ZIKV) has been concentrated in the Caribbean, Southeastern United States, and South- and Central America; resulting in travel-based cases being reported around the globe. As multi-disciplinary collaborations are combatting the ZIKV outbreak, the need to validate the sequence of existing strains has become apparent. Here, we report high-quality sequence data for multiple ZIKV strains made publicly available through the National Institutes of Health- (NIH) funded biorepository, BEI Resources (www.beiresources.org). Next-generation sequencing, 3′ rapid amplification of cDNA ends (RACE), and viral genome annotation pipelines generated GenBank sequence records for 16 BEI Resources strains. Minor variants, consensus mutations, and consensus insertions/deletions were identified within the viral stocks using next-generation sequencing (NGS) and consensus changes were confirmed with Sanger sequencing. Bioinformatics analyses of the sequencing results confirm that the virus stocks available to the scientific research community through BEI Resources adequately represent the viral population diversity of ZIKV.